HEMPEL's strategy for expansion in the Indian paint market - Christensen, Jesper Moller (2006)
The increasing purchasing power of 1,095,351,995 Indians and the growing manufacturing base for export are creating a potential for HEMPEL in India of approximately 94 million litres. 75 million litres of these are from the Protective segment where HEMPEL's new strategic goal is to be a profitable No. 1 by market share by 2011.